IMPLEMENTATION OF ISLAMIC CHARACTER EDUCATION THROUGH MORNING HABIT PROGRAM - Helmi Aziz; Rahila Rahila; Agus Halimi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2020)
This study aims to determine the background of organizing Islamic character education through a habituation program at SMP PGII 1 Bandung. Others, to find out the implementation process, the evaluation process, and also the results achieved from the habituation program. This study uses a qualitative approach with a case study method, where researchers explore programs, events, processes, and activities, to one person / more which is presented descriptively. This research shows that SMP PGII 1 Bandung organizes Islamic character education through habituation programs. The form of implementation was carried out through morning greetings, Asmaul Husna dhikr, recitation of the Qur'an, prayer, singing national compulsory songs / PGII hymns, morning inspirations, daily infaq habitation, and duha prayer. Evaluation is carried out on a daily and semester basis. This habituation program can increase the activities of students in carrying out positive habituation, because unconsciously the student routines will be recorded in the subconscious memory and become a habit in their daily lives. AbstrakPenelitian ini bertujuan untuk mengetahui latar belakang penyelenggaraan pendidikan karakter Islami melalui program pembiasaan di SMP PGII 1 Bandung.  Lainnya, untuk mengetahui proses penyelenggaraanya, proses evaluasi, dan juga hasil yang dicapai dari program pembiasaan tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, dimana peneliti melakukan eksplorasi terhadap program, kejadian, proses, dan aktivitas, kepada satu orang/lebih yang disajikan secara deskriptif. Penelitian ini menunjukkan bahwa SMP PGII 1 Bandung menyelenggarakan pendidikan karakter Islami melalui program pembiasaan. Bentuk implementasinya dilaksanakan melalui kegiatan sapa pagi, dzikir Asmaul Husna, tilawah Qur’an, do’a, menyanyikan lagu wajib nasional/hymne PGII, inspirasi pagi, pembiasaan infak harian, dan shalat dhuha. Evaluasi dilakukan secara harian dan semesteran. Program pembiasaan ini dapat meningkatkan aktifitas siswa dalam melaksanakan pembiasaan positif, karena secara tidak sadar rutinitas siswa akan terekam dalam memori alam bawah sadar dan menjadi kebiasaan dalam keseharian mereka.